PENGARUH TINGKAT PENGETAHUAN, MOTIVASI, SIKAP TERHADAP PARTISIPASI MASYARAKAT DALAM PENCEGAHAN KASUS DHF - Sunaryo Joko Waluyo; Siti Nur Solikah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The morbidity rate of DHF cases in 2017, 68,407 cases, death rate 393 people, IR rate 26.12/100 population. The incidence of DHF is influenced by many factors, one of which is community behavior due to lack of knowledge and community participation in maintaining environmental cleanliness. It is important that efforts to increase the knowledge, attitudes, and behavior of the community regarding the prevention of DHF disease with better knowledge will lead to the attitudes and behavior of the community to prevent DHF. To determine the effect of the level of knowledge, motivation, attitude towards community participation in the prevention of DHF. The research used is descriptive correlational. The sample is 30 respondents. The instrument uses a questionnaire, the analysis uses SPSS.17.0. The results of the simultaneous regression test obtained the value of sig. 0.002 < 0.05, then the independent variable simultaneously affects the dependent variable. The value of Fcount = 6.486 and Ftable = 2.95 means that F(6.486) > Ftable (2.95), there is a combined effect of the independent variables on the dependent variable. The contribution of Knowledge, Motivation, and Attitude variables is 0.758. or 75.8% while the rest (24.2%) is influenced by other variables outside the study. There is a significant influence between the level of knowledge, motivation and attitudes towards community participation in the prevention of DHF cases. To increase the active participation of the community in the prevention of DHF, health education and active motivation are needed by health workers to the community.